The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.jamda.2020.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities in Nursing Home End-of-Life Care: A Systematic Review

Abstract: Objective: Health disparities are pervasive in nursing homes (NHs), but disparities in NH end-of-life (EOL) care (ie, hospital transfers, place of death, hospice use, palliative care, advance care planning) have not been comprehensively synthesized. We aim to identify differences in NH EOL care for racial/ethnic minority residents. Design: A systematic review guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses and registered in PROSPERO (CRD42020181792). Setting and Participants: O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 54 publications
2
22
2
Order By: Relevance
“…Our study found significant racial and socioeconomic disparities in HDAH at the EOL, consistent with a large evidence base documenting disparity in care across a range of disciplines. [36][37][38] In our study, HRRs with higher poverty rates had a greater total number of HDAH, which differs from the findings of a similar study conducted in Canada. 17 It is not clear why individuals in poverty experienced greater HDAH in our cohort, but further study is warranted to understand the drivers of this pattern and ensure that these individuals are able to access appropriate and necessary care that could improve quality of life at the EOL.…”
Section: Hrr Characteristics Associated With Hdah At Eolcontrasting
confidence: 99%
“…Our study found significant racial and socioeconomic disparities in HDAH at the EOL, consistent with a large evidence base documenting disparity in care across a range of disciplines. [36][37][38] In our study, HRRs with higher poverty rates had a greater total number of HDAH, which differs from the findings of a similar study conducted in Canada. 17 It is not clear why individuals in poverty experienced greater HDAH in our cohort, but further study is warranted to understand the drivers of this pattern and ensure that these individuals are able to access appropriate and necessary care that could improve quality of life at the EOL.…”
Section: Hrr Characteristics Associated With Hdah At Eolcontrasting
confidence: 99%
“…51 Black and African American residents often have multiple, complex, chronic conditions while approaching the end of life but receive worse end-of-life care than White older adults. 52 Despite the increased need for nursing home care among older adults, nursing homes are costly, and to qualify for Medicaid, individuals often need to “spend down” assets to receive coverage. 53 …”
Section: Resultsmentioning
confidence: 99%
“…Reviews investigating self-management of pain have revealed ethnic differences in coping strategies, behaviours, communication and delays in help-seeking [ 42 , 44 – 46 ]. Previous systematic literature reviews examining race and ethnicity within palliative care have investigated issues such as, access to hospice and advanced care planning, but none have specifically focused on pain management in advanced disease [ 47 51 ].…”
Section: Introductionmentioning
confidence: 99%